Synthesis, Characterization and Crystal Structure of New Mixed-Anions of Bismuth(III) Complexes - Taheri, Syavash; Morsali, Ali (Asian Journal of Chemistry, 2016)
Complexes [Bi(bpy)2(NO3)(NCS)2], [Bi(bpy)2(NO3)(NCS)] and [Bi(bpy)Br4]–(bpyH+) have been synthesized by reaction of Bi(NO3)3 and ligands using a direct synthetic method. The complexes have been isolated and characterized by CHN elemental analysis, IR 1H and 13C NMR spectroscopy. The structure of the [Bi(bpy)Br4]–(bpyH+) has been confirmed by X-ray crystallography. The single crystal X-ray data of this compound shows that the complex is monomeric and the Bi atom has an unsymmetrical six-coordinate geometry, being coordinated by four Br atoms and two nitrogen atoms of the 2,2´-bipyridine ligand. The arrangement of the 2,2´-bipyridine ligand and Br atoms exhibits a coordination gap around the Bi(III) ion, occupied possibly by a stereoactive lone pair of electrons on bismuth(III). There is one 2,2´-bipyridinium (bpyH+) cation that was not coordinated to the bismuth atom. The uncoordinated 2,2´-bipyridinium (bpyH+) cations help in forming the p-p stacking interaction between the parallel aromatic rings belonging to adjacent chains n the compound.